Recollections of home : a study of the use of domestic objects and needlework in contemporary jewellery and my art practice - Van der Merwe, Catrina (Nini) (Stellenbosch : Stellenbosch University, 2013)
Thesis (MA)--Stellenbosch University, 2013.